PEMBERDAYAAN PEREMPUAN MELALUI KOPERASI WANITA DI BANDA ACEH - T Lembong Misbah (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2015)
Women empowerment through Woman Econamic Enterprise or Economic Enterprise which is handled by women and in Banda Aceh, has demonstrated its ability to build the economy of the members. However,only a few of Woman Econamic Enterprise in Banda Aceh which operates and only a few of Economic Enterprise which is running according to Economic Enterprise rules. Women Economic Enterprise in Jakarta Surabaya, Jakarta, Lombok and other areas have run very good and normally get over of hundreds of billions in a year. Based on their experience it does not close the opertunity for Aceh especially in Banda Aceh to develop Women Economic Enterprise, because it is one of the important place for women to empower themselves, especially in managing the economic life of the family and society to be better.